Webinar Partisipatif: Implementasi Mindful Learning dalam Layanan Konseling - Moesarofah, Moesarofah; Mudhar, Mudhar; Hartono, Hartono; Muwakhidah, Muwakhidah (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract In the context of education in the digital era, many students experience increased stress due to high academic demands and distractions from the use of digital technology. The use of digital devices, although it provides many advantages, also increases the risk of impaired concentration and student learning motivation. This participatory webinar aims to implement mindful learning in counseling services. The service design uses participatory webinars, integrates the principles of Community-Based Participatory Research, and maximizes the interaction and involvement of 290 participants consisting of lecturers, teachers, and BK students. The activity was carried out online on March 8-10, 2025. The results showed the effectiveness of the webinar in improving the understanding and skills of BK teachers about mindful learning, with a significant increase after the webinar. This implementation has a positive impact on clients, including increasing self-awareness, emotional regulation, and interpersonal relationships. The contribution of the activity is related to the development of a collaborative network between BK teachers, while the implications of the activity are related to the development of ongoing training and mentoring programs for BK teachers.